FKKT Navdih Znanosti – Študij na FKKT: Druga izdaja (University of Maribor Press, 2024)
FCCE Inspired by Science – Study at FCCE (Second edition). The brochure presents the study at FCCE UM, presents the vision and mission of the faculty, the possibilities of continuing studies and job opportunities, as well as the presentation of course syllabus at all levels and study programmes.